Islamic Leadership in the Digital Era: Mapping Intellectual Structure and Emerging Research Trends - Rosita Damayanti; Ika Nurul Qamari (Smart Society, 2026)
The growing integration of digital technologies into organizational and social life has reshaped leadership practices, creating new challenges and opportunities for Islamic leadership. Although studies on Islamic leadership have increased substantially over the past decade, a comprehensive understanding of its intellectual structure, thematic evolution, and emerging research directions in the digital era remains limited. This study aims to map the development of Islamic leadership research, identify dominant themes, and explore emerging trends and future research opportunities. Using a Systematic Literature Review (SLR) combined with bibliometric analysis, data were retrieved from the Scopus database using the keyword “Islamic leadership” for publications between 2010 and 2025. Following the PRISMA protocol, 69 eligible articles were selected from an initial dataset of 1,880 records and analyzed using VOSviewer. The findings reveal that Islamic leadership research has experienced steady growth, particularly since 2022, with dominant themes focusing on employee performance, job satisfaction, motivation, organizational commitment, and Islamic work ethics. The intellectual landscape is largely shaped by contributions from Southeast Asian countries, especially Indonesia and Malaysia, while increasing international collaboration has expanded the field across Europe, Australia, and the Americas. Furthermore, the analysis identifies emerging research fronts related to digital transformation, workplace spirituality, knowledge sharing, and transformational leadership, indicating a shift from predominantly normative perspectives toward more contextual and adaptive approaches to contemporary organizational challenges. This study contributes to the literature by providing a comprehensive mapping of the intellectual structure and thematic evolution of Islamic leadership research and by proposing future directions for integrating Islamic leadership principles with digital-era organizational practices. The study is limited to Scopus-indexed publications and a specific search strategy, suggesting opportunities for future studies to incorporate broader databases and complementary analytical approaches.